THE REASONS OF STUDENTS REALIZING THEIR ATTITUDES TOWARD ENGLISH CONVERSATIONS CLASS - Mara Sutan Siregar; Amrin Saragih; Rahmad Husein (Universitas Negeri Medan, 2019)
English conversation is an important lesson for Senior High School students in order to face the globalization effects. Many students considered English conversation as a controversial lesson through their positive and negative attitudes toward it. This study aimed to reason for the Senior High School students realize their attitudes toward English conversation class in the ways they are. This qualitative study was conducted at the twelfth grade of Senior High School students. The subjects of this study were 20 students consisting of 11 females and 9 males at the age of 16-18 years old. The data were collected by observations and interviews then were analyzed using Interactive Models. The result showed that there were four reasons of the students realized their attitudes i.e. the (1) language pride, (2) awareness of language norms, and the new findings were (3) motivation to get the job, and (4) lack of skill. It was concluded that the students’ attitudes varied as to positive and negative ones and realized in numerous manners affected by several factors.Keywords: language, attitudes, conversations